RELIGIOUS DEVIANCE AND SPIRITUAL ABUSE ISSUES: A CRITICAL REVIEW - Md Yusoff, Yusmini; Tengku Kasim, Tengku Sarina Aini; Baharuddin, Madiha (Journal of Al-Tamaddun, 2018)
This article highlights on abusive issues within religious deviant groups. It argues that abusive behavior is apparently driven by illegitimate purpose and means. The argument put forth is that practices of abuse may stem from the discursive construction of fanaticism/extremism that leads to spiritual harm and abuse to those who involved. In order to assess the relative value of these issues, a systematic review of literatures is employed as a research method. Therefore, both online databases and the references lists of articles were searched using predefined search-terms such as religious deviance, deviant group, cult, spiritual abuse, and discourse of fanaticism and extremism. A key finding of these issues is that fanaticism/extremism appears to be a consistent factor of abusiveness in religious deviant groups.